2002
DOI: 10.1001/archsurg.137.7.833
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Histological Assessment of Surgical Margins in Resected Liver Metastases From Colorectal Carcinoma

Abstract: There have been few reports on the minimum surgical margins (SMs) required for successful liver resection in patients with colorectal metastases. This minimum requirement may be narrower than the previously recommended margin of 10 mm.Objectives: To identify the minimum margins by assessing the presence of micrometastases around the tumor using genetic and histological techniques, and to investigate whether SMs are associated with patterns of tumor recurrence or patient survival. Design: Prospective and retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
154
3
32

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(200 citation statements)
references
References 21 publications
11
154
3
32
Order By: Relevance
“…Patients with positive margins were excluded from the current meta-analysis and only patients with negative margins were included. Many studies sub-stratified sub-centimeter negative margins into different sub-categories [4,8,10]. For these studies, a weighted mean was calculated using the number of patients in each sub-category and the corresponding percentage survival, to compute percentage survival for the whole <1 cm negative margin sub-group.…”
Section: Data Extraction and Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with positive margins were excluded from the current meta-analysis and only patients with negative margins were included. Many studies sub-stratified sub-centimeter negative margins into different sub-categories [4,8,10]. For these studies, a weighted mean was calculated using the number of patients in each sub-category and the corresponding percentage survival, to compute percentage survival for the whole <1 cm negative margin sub-group.…”
Section: Data Extraction and Definitionsmentioning
confidence: 99%
“…Hepatic resection remains a well accepted modality in the treatment of patients with colorectal liver metastases (CRLM) with 5 year overall survival (OS) ranging from 37 % to 58 % [1][2][3][4] and 5 year disease free survival (DFS) ranging from 11 % to 50 % [3,[5][6][7][8][9][10][11][12][13][14]. Recurrence of the disease after resection still remains a challenge and adversely affects the long term outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14, 38,39,41 Many scoring systems for predicting the outcome of resection of CRC liver metastases are based on long-lasting retrospective studies that started before new potent chemotherapeutical agents were introduced as well as before refined imaging techniques used today were developed and before sophisticated surgical techniques were routinely used. A special problem arises from the fact that ongoing studies of adjuvant chemotherapy for patients with resected or ablated CRC liver metastases will not be reported for several years.…”
Section: Prognostic Evaluation Patient Selection and Recent Advancesmentioning
confidence: 99%
“…Kokudo demonstrated that CRC liver metastases can grow crossing intersegmental planes, without infiltrating the parenchyma and with minimal lateral spread. 41 Based on such observations Kokudo concludes that anatomic resection for CRC liver metastases is neither necessary nor beneficial and that analogy with operations for HCC is not accurate. 65 In another paper Kokudo concludes that there is no significant difference in survival between anatomical major resection and non-anatomical limited resection for CRC liver metastases.…”
mentioning
confidence: 99%